Diagnosis of child abuse in dental care: An analysis of oral manifestations and indicators of mistreatment (Research, Society and Development, 2023)
A literature review was carried out on the diagnosis of child abuse in dental care. This type of study allows the search, evaluation and condensation of available evidence on a given topic to be carried out. Child abuse stands out for its various forms, comprising physical, sexual, emotional abuse, neglect and exploitation, which leave physical and psychological marks, in addition to being a problem with a major impact on society. The dentist is usually the first health professional to detect signs of child abuse because of the orofacial region, which is the most affected, with emphasis on physical and sexual abuse, as they can be present in the head and neck region, presenting as an oral manifestation: STD (sexually transmitted disease) injuries, hemorrhage secondary to fellatio and physical characteristics such as soft tissue ruptures, tooth avulsion, ecchymosis, hematoma and burns. The importance of early diagnosis and compulsory notification is considered and the importance of calling a dentist in this regard is highlighted. The objective of this work is to diagnose signs and symptoms in dental care, as well as guide dental surgeons on recognition and compulsory notification of possible mistreatment.